2022
DOI: 10.3390/jcm11237220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Curcumin Derivative on YAP Pathway against Ovarian Cancer

Abstract: The purpose of this study is to study the effect of curcumin derivative WZ10 on the proliferation, invasion and apoptosis of ovarian cancer OVCAR3 cells, and to explore its mechanism. MTT assay was used to detect the effect of WZ10 on the proliferation of ovarian cancer OVCAR3 cells; Annexin V/PI double staining flow cytometry was used to detect the effect of WZ10 on cell apoptosis; Transwell method was used to detect the effect of WZ10 on cell invasiveness; Western blot was used to investigate the effect of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The role of curcumin as a cancer chemopreventive agent has been rigorously studied in various cancer models. [20][21][22][23][24] Recent studies have highlighted curcumin's antiproliferative and antimotility effects on breast cancer cells, yet the intricate molecular mechanisms underlying these actions require further elucidation. [25][26][27] Therefore, exploring curcumin's influence on cell motility, proliferation, cell cycle, and apoptosis, particularly in TNBC, and uncovering its molecular underpinnings are of paramount clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The role of curcumin as a cancer chemopreventive agent has been rigorously studied in various cancer models. [20][21][22][23][24] Recent studies have highlighted curcumin's antiproliferative and antimotility effects on breast cancer cells, yet the intricate molecular mechanisms underlying these actions require further elucidation. [25][26][27] Therefore, exploring curcumin's influence on cell motility, proliferation, cell cycle, and apoptosis, particularly in TNBC, and uncovering its molecular underpinnings are of paramount clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts its anticancer effects by modulating multiple targets, such as negative regulation of tumor metastasis, angiogenesis, apoptosis, cell cycle progression, in ammation, and multidrug resistance pathways. It has been intensively studied as a cancer chemopreventive agent in various cancer models [13][14][15][16][17]. A recent study found that curcumin has potential anti-proliferative and motility effects against breast cancer, and its speci c molecular mechanism remains to be further explored [18][19][20].…”
Section: Discussionmentioning
confidence: 99%